Non-adherence to malaria prophylaxis: The influence of travel-related and psychosocial factors - Jolanda G.M. Hoefnagel; Karlijn Massar; Jeannine L.A. Hautvast (Elsevier, 2020)
Background: The effectiveness of malaria chemoprophylaxis is limited by a lack of compliance in travellers. This study assesses the demographic, travel-related, and psychosocial determinants of non-compliance with chemoprophylaxis. Methods: 715 adults, who received a pre-travel malaria prophylaxis prescription, were invited to complete a post-travel digital questionnaire on non-compliance, demographics, travel-related and psychosocial variables. Results: 330 travellers (53% response) reported 32% non-compliance with malaria chemoprophylaxis. Logistic regression analyses revealed that 3/11 assessed psychosocial variables uniquely predicted non-compliance: 'negative attitude towards chemoprophylaxis' (β = 0.694, OR 2.0, p < 0.01), 'low perceived severity of malaria' (β = 0.277, p = 0.04) and 'fatigue during travel' (β = 2.225, OR 9.3, p < 0.01). Furthermore, the age and education of the traveller were uniquely predictive of non-compliance (β = −0.023 (p = 0.02) and β = 0.684 (p = 0.04)). None of the travel-related variables predicted non-compliance. Conclusions: About one-third of the travellers in our study were non-compliant with malaria prophylaxis, especially young travellers and highly educated travellers. Fatigue during travel seems to lead to non-compliance. Further research should focus on addressing the psychosocial factors in pre-travel consultation, since these appear to be better predictors for intention to comply than travel-related variables. Keywords: Medication adherence, Patient compliance, Atovaquone, Proguanil, Health behaviour, Health knowledge attitudes practice, Antimalarials